ENTREPRENEURSHIP FOR DEVELOPING SMALL AND MEDIUM-SCALE FARMERS IN AGRICULTURAL CLUSTER - Silfia Silfia; Helmi Helmi; Melinda Noer; Henmaidi Henmaidi (TRIKONOMIKA, 2020)
The entrepreneurship possesses the energy to generate innovation and improvement of agricultural clusters. However, it somehow has yet been successful to reach marginalized groups including Small and Medium Enterprises (SMEs) in agricultural clusters. The research questions to be addressed are thus: (1) how public policy at both national and regional levels contribute to entrepreneurship capacity-building in developing agricultural cluster in order to achieve SMEs empowerment. (2) Empiric actuality of entrepreneurship in agricultural cluster development. The research is a qualitative-descriptive research, case study on agricultural cluster at Subdistrict Lembah Gumanti of Solok Regency in the province of West Sumatra. Research result indicates that entrepreneurship policy has indeed yet at its best in the development of SME-based agricultural clusters due to the fact that entrepreneurial policy in agricultural clusters is still dominated by personal/private and corporation-based entrepreneurship.